Plausibility of super high-flux dialyzer reuse in maintenance hemodialysis - Prapunwatana, Piyapun; Thongsricome, Thana; Leelahavanichkul, Asada; Injan, Patcharin; Chariyavilaskul, Pajaree; Susantitaphong, Paweena; Avihingsanon, Yingyos; Eiam-Ong, Somchai; Tiranathanagul, Khajohn (Frontiers in Medicine, 2025)
BackgroundDialyzer reuse in traditional hemodialysis (HD) has been demonstrated to reduce medical waste and manufacturing costs compared to a single-use strategy. HD techniques nowadays have increasingly shifted to convective therapies, such as HD with super high-flux dialyzers (SHF), to remove larger uremic toxins and improve outcomes. However, studies on the reuse of SHF are lacking. Successful reuse of SHF may lower the economic and environmental burdens while maintaining superior clinical outcomes.ObjectiveTo compare the removal of uremic toxins and safety after reuse of SHF.MethodsELISIO-21 HX SHF were reprocessed with peracetic acid for up to 15 reuse times in stable thrice-a-week HD patients in King Chulalongkorn Memorial Hospital. The reduction ratio (RR) or clearance of β2-microglobulin (β2M, 11.8 kDa), α1-microglobulin (α1M, 31 kDa), λ-free light chain (λFLC, 45 kDa), and protein-bound indoxyl sulfate were compared between the 1st, 2nd, 5th, 10th, and 15th reuse times. Dialysate albumin loss and the change in serum albumin were assessed.ResultsA total of 15 dialyzers were investigated from 5 patients. The β2M clearance and RR were comparable between the 1st and 15th use (127.2 ± 18.3 mL/min vs. 114.4 ± 17.2 mL/min, p-value 0.93 and 85.5% ± 5.9% vs. 82.5% ± 3.5%, p-value 1.00, respectively). The λ-FLC and indoxyl sulfate RR significantly reduced while α1M RR remained unchanged across the study period. Dialysate albumin loss decreased significantly from 1.01 g during the 1st use to 0.19 g during the 2nd and 0.06 g during the 5th use (p-value < 0.001). However, there was no statistically significant change in serum albumin. No adverse effect was observed throughout the study.ConclusionSuper high-flux dialyzers reuse is a safe and promising method to reduce medical waste and manufacturing costs while maintaining the benefits of this novel HD technique. We also suggest appropriate cut-off points for the change in RR of the middle-molecule uremic toxin after reuse to prevent significant impairment in solute clearances.